The Role of Non-Timber Forest Products for Livelihood diversification in Bundelkhand Region of Uttar Pradesh - Panda, L. R. Lakshmikanta; Uniyal, Arun; Kukreti, Jyoti; Ritu; Singh, Neelu (International Journal of Economic Plants, 2024)
Various local communities living in India have been dependent on forests for centuries. The contribution of non timber forest products (NTFPs) has been recognized globallyfor their role in preservation, income generation, livelihood enhancement and rural development. About 275 million poor rural people in various regions of India are dependent on non-timber forest produce. The present study was conducted duringthe month of January to November 2022 to assess the major NTFPs and their role in livelihood generation in Bundelkhand region of Uttar Pradesh. Through surveys and interviews conducted in 4 study area (Viz. Banda, Jhansi, Mahoba and Chitrakut) of Bundelkhand, among the people of local communities, it has been revealed that even today the people of study area show their dependency on forest based NTFPs. Through harvesting, collection and processing of non-timber forest produce, providing new employment opportunities in the Bundelkhand region of India. In this region local people provide an overview of the dependency of different rural communities on NTFP’s such as salai gum, kullu gum, flowers and fruit of Mahua, baskets from bamboo and Harsingar, bidi from tendu leaves, Chironji seeds, jhadu from Date palm leaves, Amla, Bahera, Satavar and Nagarmotha for sustain their livelihood. Despite their significance to employment, NTFP markets are mostly informal andscattered, with no proper records maintained, leading to an insufficient information flowon the contribution of NTFP trade at the local as well as national level. There is an urgent need to promote all these things today so that the income of local collectors can be improved.